Unbecoming - Downham, Jenny (David Fickling Books/Scholastic Inc., 2016)
Life has just become very complicated for seventeen-year-old Katie; her father walked out a year ago, her mother is stressed out, her brother is a "special needs" teenager, and she is caring for the maternal grandmother she has never met, who is suffering from Alzheimer's-and Katie has a secret of her own that she cannot reveal.